Cell-targeted PD-1 agonists are potent NK-cell inhibitors - Harriet C. Pope; Harriet C. Pope; Ana L. Chiodetti; Alice Newey; Guillaume Rieunier; David X. Overton; Eduardo Mateos-Diaz; Tara M. Mahon; Giovanna Bossi; Hussein Al-Mossawi; Charlotte Viant (Frontiers in Immunology)
BackgroundThe programmed cell death protein 1 (PDCD1 or PD-1) is a key regulatory immune checkpoint and a major target for therapeutic intervention. In oncology, antibodies blocking the PD-1 pathway are used to activate immune cells to promote anti tumour immunity while in immune-mediated inflammatory diseases, PD-1 agonist molecules have the potential to achieve immune suppression. NK cells are a specialised population of innate lymphocytes able to recognize a large range of distressed cells including damaged tissues in autoimmune and inflammatory conditions. Of note, NK cells can upregulate PD-1 expression upon activation and their effector functions can be modulated by the PD-1 signalling pathway.MethodsWe have generated a novel bispecific inhibitory molecule, comprised of a targeting domain highly specific for a pre-pro-insulin peptide presented by the HLA-A*02 molecules on the cell surface of pancreatic β-cells and a PD-1 agonist effector domain. Suppressive effects of the β-cell tethered bispecific PD-1 agonist molecule on NK cells and NK92-PD-1 cell line activation were assessed through gene expression, cell surface expression of the CD107a degranulation marker, intracellular IFNγ production and Granzyme B secretion. EndoC-b cells proliferation and insulin production were also measured.ResultsWe observed that the bispecific PD-1 agonist molecules tethered to pancreatic b-cells accumulate at the immunological synapse, modify NK cell gene expression and decrease their inflammatory and cytotoxic functions.ConclusionsTargeted PD-1 agonist molecules, inhibiting T cells and NK cells in a tissue-specific manner offer a new promising treatment for autoimmune and inflammatory diseases.